Assessment of interleukin-10 promoter variant (−1082A/G) and cytokine production in patients with hemolytic uremic syndrome - Mongelos, Micaela Aldana; Sosa, Fernando Nicolás; Pineda, Gonzalo Ezequiel; Fiorentino, Gabriela; Santiago, Adriana; Abelleyro, Miguel Martín; Rossetti, Liliana Carmen; Exeni, Ramón; De Brasi, Carlos Daniel; Palermo, Marina Sandra; Ramos, María Victoria (Frontiers in Pediatrics, 2023)
Introduction: Hemolytic Uremic Syndrome (HUS) produces acute kidney failure mainly in children, caused by Shiga toxin-producing E. coli and inflammatory response. Although anti-inflammatory mechanisms are triggered, their implication in HUS is scarce. Interleukin-10 (IL-10) regulates in vivo inflammation and the interindividual differences in its expression are related to genetic variants. Particularly, the single nucleotide polymorphism (SNP) rs1800896 -1082 (A/G), located in the IL10 promoter, regulates cytokine expression. Methods: Plasma and peripheral blood mononuclear cells (PBMC) were obtained from healthy children and HUS patients characterized by hemolytic anemia, thrombocytopenia and kidney damage. Monocytes identified as CD14+ cells were analyzed within PBMC by flow cytometry. IL-10 levels were quantified by ELISA and SNP -1082 (A/G) was analysed by Allele Specific-PCR. Results: Circulating IL-10 was increased in HUS, but PBMC from these patients exhibited a lower capacity to secrete this cytokine compared to healthy children. Interestingly, there was a negative association between IL-10 and the inflammatory cytokine IL-8 circulating levels. We observed that circulating IL-10 was three-fold higher in HUS patients with allele -1082G in comparison to genotype AA. Moreover, there was a relative enrichment of genotypes GG/AG in HUS patients with severe kidney failure. Discussion: Our results suggest a possible contribution of SNP -1082 (A/G) to the severity of kidney failure in HUS that should be further evaluated in a larger cohort.